UJI EFEK ANALGESIK EKSTRAK ETANOL DAUN GEDI (Abelmoschus manihot (L.) Medik) PADA MENCIT (Mus musculus) - Pratiwi, Ristanti; Posangi, Jimmy; ., Fatimawali (e-Biomedik, 2013)
Abstract: The objectives of the research were to find out the analgesic effect of giving Gedi (Abelmoschus manihot (L.) Medik) leaf ethanol extract orally on the number of writhing after thermal pain induction of mice. This research using 15 mice which is divided into 5 groups consisted of 1 negative control group given by the aquades, 1 positive control group given by the tramadol, and 3 experiment groups. Experiment group given by Gedi (Abelmoschus manihot (L.) Medik) leaf ethanol extract with the doses which different each other, that is 30 mg/30 g BW, 60 mg/30 g BW and 120 mg/30 g BW. Thermal pain induction was done by placing the mice on hot plate constant temperature of 550C. The mice gave respond in the way of lick its foot or even jumping. The data was collected using table, graphic and analyzed using one direction ANOVA model and it was continued with LSD test to find out the difference every treatment group. The result of analysis showed that gedi’s leaf ethanol extract have the analgesic effect and the maximum effect presented at gedi leaf ethanol extract dosage 60 mg/30 g BW. Keywords: Gedi’s leaf, analgesic effect    Abstrak: Tujuan penelitan ini yaitu menemukan efek analgesik dari pemberian ekstrak etanol daun gedi (Abelmoschus manihot (L.) Medik) peroral pada mencit yang kemudian diamati jumlah geliatnya setelah diinduksi panas. Penelitian ini menggunakan 15 ekor mencit yang dibagi 5 kelompok yang terdiri dari 1 kelompok kontrol negatif yang diberi aquades, 1 kelompok kontrol positif yang diberi tramadol, dan 3 kelompok eksperimen. Kelompok eksperimen diberi ekstrak etanol daun gedi dengan dosis yang berbeda-beda, yaitu 30 mg/30 g BB, 60 mg/30 g BB, dan 120 mg/30 g BB. Induksi nyeri berupa panas dilakukan dengan meletakkan mencit pada hot plate dengan suhu 550C . Mencit memberi respon berupa menjilat kaki dan atau melompat. Data disajikan berupa tabel, grafik dan menggunakan analisis statistik ANOVA yang dilanjutkan dengan LSD untuk menemukan perbedaan dari setiap kelompok. Hasil analisis menunjukkan bahwa ekstrak etanol daun gedi memiliki efek analgesik dan efek maksimumnya didapatkan pada dosis 60 mg/30 g BB. Kata kunci: Daun gedi, efek analgesik